High Levels of Retention in Care with Streamlined Care and Universal Test-and-Treat in East Africa - Brown, Lillian B.; Havlir, Diane V.; Ayieko, James; Mwangwa, Florence; Owaraganise, Asiphas; Kwarisiima, Dalsone; Tamara, Clark; Bukusi, Elizabeth A.; Kamya, Moses R.; Petersen, Maya L.; Charlebois, Edwin D.; The Search Collaboration (AIDS, 2016)
We sought to measure retention in care and identify predictors of non-retention among patients receiving ART with streamlined delivery during the first year of the ongoing SEARCH “test-and-treat” trial (NCT 01864603) in rural Uganda and Kenya. Prospective cohort of patients in the intervention arm of the SEARCH Study. We measured retention in care at 12 months among HIV-infected adults who linked to care and were offered ART regardless of CD4 cell count, following community-wide HIV-testing. Kaplan-Meier estimates and Cox proportional hazards modeling were used to calculate the probability of retention at one year and identify predictors of non-retention. Among 5,683 adults (age ≥ 15) who linked to care, 95.5% (95% CI: 92.9 – 98.1%) were retained in care at 12 months. The overall probability of retention at one year was 89.3% (95% CI: 87.6 – 90.7%) among patients newly linking to care and 96.4% (95% CI: 95.8 – 97.0%) among patients previously in care. Younger age and pre-ART CD4 below country treatment initiation guidelines were predictors of non-retention among all patients. Among those newly linking, taking more than 30 days to link to care after HIV diagnosis was additionally associated with non-retention at one year. HIV viral load suppression at 12 months was observed in 4,227/4736 (89%) of patients retained with valid viral load results. High retention in care and viral suppression after 1 year were achieved in a streamlined HIV care delivery system in the context of a universal test-and-treat intervention.
Keywords: HIV, Africa, Antiretroviral therapy, Healthcare, Retention in care